Design and production of TBEV specific cleavage reporter for in vitro and in cell studies - Huszárová, Eliška (Jihočeská univerzita, 2022)
Tick-borne encephalitis virus (TBEV) is an important human pathogen and as of now, there are no specific therapeutics to combat this disease. In vitro and in cell models are essential in studying the disease and in the pursuit of novel therapeutics. This thesis deals with the design and production of two genetically encoded cleavage reporters of TBEV NS2B-NS3 protease activity. The reporters were produced in E. coli and tested with recombinant NS2B-NS3 protease, as well as produced in mammalian cell lines and analyzed for fluorescence upon infection with TBEV.
Design and production of TBEV specific cleavage reporter for in vitro and in cell studies
Keywords: TBEV; NS2B-NS3 protease; cleavage reporter; PAmCherry